Compressive and tensile strain sensing using a polymer planar Bragg grating - Rosenberger, M.; Hessler, S.; Belle, S.; Schmauß, Bernhard; Hellmann, R. (Optics Express, 2014)
A polymer planar Bragg grating sensor is used for measuring both mechanical compressive and tensile strain. The planar waveguide with integrated Bragg grating is fabricated in bulk Polymethylmethacrylate in a single writing step using combined amplitude and phase mask technique. After butt coupling of a single-mode optical fiber the planar structure can be applied for measuring both mechanical tensile and compressive strain alongside the integrated waveguide without the need of further modifications. In this respect, we particularly report for the first time compressive strain measurements using a polymer Bragg grating. Furthermore, the sensitivity of the sensor against tensile and compressive strain, its reproducibility and hysteresis are investigated and discusse
lhft_intern.bib::Rosenberger2014b